Establishing a Southern Swedish Malignant Melanoma OMICS and biobank clinical capability. Issue 1 (27th February 2013) - Welinder, Charlotte; Jönsson, Göran; Ingvar, Christian; Lundgren, Lotta; Olsson, Håkan; Breslin, Thomas; Végvári, Ákos; Laurell, Thomas; Rezeli, Melinda; Jansson, Bo; Baldetorp, Bo; Marko‐Varga, György
Abstract: Background: The objectives and goals of the Southern Swedish Malignant Melanoma (SSMM)are to develop, build and utilize cutting edge biobanks and OMICS platformsto better understand disease pathology and drug mechanisms. The SSMMresearch team is a truly cross‐functional group with members from oncology, surgery, bioinformatics, proteomics, and genomics initiatives. Within theresearch team there are members who daily diagnose patients with suspectmelanomas, do follow‐ups on malignant melanoma patients and remove primaryor metastatic lesions by surgery. This inter‐disciplinary clinical patientcare ensures a competence build as well as a best practice procedure wherethe patient benefits. Methods: Clinical materials from patients before, during and after treatments withclinical end points are being collected. Tissue samples as well as bio‐fluidsamples such as blood fractions, plasma, serum and whole blood will bearchived in 384‐high density sample tube formats. Standardized approachesfor patient selections, patient sampling, sample‐processing and analysisplatforms with dedicated protein assays and genomics platforms that willhold value for the research community are used. The patient biobank archivesare fully automated with novel ultralow temperature biobank storage unitsand used as clinical resources. Results: An IT‐infrastructure using a laboratory information management system (LIMS)has been established, that is the key interface for the research teams inorder to share and explore data generated within the project. The cross‐sitedata repository in Lund forms the basis for sample processing, together withbiological samples in southern Sweden, including blood fractions and tumortissues. Clinical registries are associated with the biobank materials, including pathology reports on disease diagnosis on the malignant melanoma(MM) patients. Conclusions: We provide data on the developments of protein profiling and targeted proteinassays on isolated melanoma tumors, as well as reference blood standardsthat is used by the team members in the respective laboratories. These pilotdata show biobank access and feasibility of performing quantitativeproteomics in MM biobank repositories collected in southern Sweden. Thescientific outcomes further strengthen the build of healthcare benefit inthe complex challenges of malignant melanoma pathophysiology that isaddressed by the novel personalized medicines entering the market.